Digital Sustainability in the Fourth Industrial Revolution - Vasja Roblek; Maja Meško; Zlatka Meško Štok (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The fourth industrial revolution launched digitalization in manufacturing sector, business and human environment. This opens a question of influence to development of the digital sustainability concept and resource-efficiency in the focus on the design of smart cities and smart factories. Furthermore, it is also necessary to respect ethical rules when using private information. These factors are fundamental framework conditions for successful products. The aim of this paper is to present the known theory and practices of digital sustainability in the fourth industrial revolution and to investigate the changes that result from digital sustainability and influence on the corporate social digital responsibility development. In order to achieve this objective, a comprehensive review of journal articles, conference papers, books and edited volumes will be performed.
Keywords: O3; O33; 330; Fourth industry revolution; digital sustainability; corporate social digital responsibility; smart city; smart products; innovation; ICT